PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN KOMPENSASI KERJA TERHADAP KINERJA KARYAWAN PT. ASTRA CABANG BIMA - Victor Heri; Hermanto Hermanto; Lina Warlina (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to analyze the partial and simultaneous effect of leadership style, communication and compensation on the performance of employees of PT. Astra Bima Branch. This study used a census sample technique, namely the entire population of 53 employees of PT. Astra Branch Bima was used as the research sample. The instrument of this research was a questionnaire using a Likert scale, and before being used to collect data, the validity and reliability tests were carried out, then the data were analyzed using multiple linear regression. The results showed that: (1) leadership style had a positive and significant effect on employee performance. This shows that there is a good leadership style as expected by subordinates so that the cause of improving employee performance; (2) communication has a positive and significant effect on employee performance. The higher employee performance satisfaction with communication within the company, the impact on increasing the quality and quantity of employee work in the company; (3) compensation has a positive and significant effect on employee performance. The more satisfied employees are with the compensation received will have an impact on morale so that employees will be more motivated in improving their performance; and (4) leadership style, communication and compensation have a simultaneous and significant effect on employee performance. This means that improving employee performance can be done through leadership style, communication and proportional compensation, not only financial compensation but also non-financial compensation. Therefore, company directors should be able to adjust the leadership style to the situation or the employee's work environment so that it can stimulate employee work motivation.